Australia : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This Selected Issues paper on Australia highlights the IMF's new Global Integrated Monetary and Fiscal Model (GIMF), which is used to examine the macroeconomic implications of alternative fiscal responses to higher revenue. Lower labor and capital income taxes, along with higher public investment, will generate the largest economic gains in the long term. The model shows that saving a portion of the additional revenue in the short term can help alleviate demand pressures and increase overall domestic savings.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet